The School administrators' perception on the leadership capabilities of the subject coordinators in Cavite Diocese Parochial Schools Association - Aribal, Roy C. (Manila : National University, 2015)
The purpose of the study was to look into the leadership capabilities of the subject coordinators of Cavite Diocese Parochial Schools Association (CADIPSA) as perceived by the school administrators.
Chapter 1. The Problem and its background -- Chapter 2. Review of related literature and studies -- Chapter 3. Methodology -- Chapter 4. Presentation, Analysis and interpretation of data -- Chapter 5. Summary, Conclusion and recommendation.
Includes bibliographical references.